pSIG plasmids, MoClo-compatible vectors for efficient production of chimeric double-stranded RNAs in Escherichia coli HT115 (DE3) strain - Ching-Feng Wu; Li-Pang Chang; Chan Lee; Ioannis Stergiopoulos; Li-Hung Chen (Plant Methods)
Abstract Background Spray-induced gene silencing (SIGS) is a promising strategy for controlling plant diseases caused by pests, fungi, and viruses. The method involves spraying on plant surfaces double-stranded RNAs (dsRNAs) that target pathogen genes and inhibit pathogen growth via activation of the RNA interference machinery. Despite its potential, significant challenges remain in the application of SIGS, including producing large quantities of dsRNAs for field applications. While industrial-scale dsRNA production is feasible, most research laboratories still rely on costly and labor-intensive in vitro transcription kits that are difficult to scale up for field trials. Therefore, there is a critical need for highly efficient and scalable methods for producing diverse dsRNAs in research laboratories. Results This study introduces pSIG plasmids, MoClo-compatible vectors designed for efficient dsRNA production in the Escherichia coli RNase III-deficient strain HT115 (DE3). The pSIG vectors enable the assembly of multiple DNA fragments in a single reaction using highly efficient Golden Gate cloning, thereby allowing the production of chimeric dsRNAs to simultaneously silence multiple genes in target pests and pathogens. To demonstrate the efficacy of this system, we generated 12 dsRNAs targeting essential genes in Botrytis cinerea. The results revealed that silencing the Bcerg1, Bcerg2, and Bcerg27 genes involved in the ergosterol biosynthesis pathway, significantly reduced fungal infection in plant leaves. Furthermore, we synthesized a chimeric dsRNA, Bcergi, that incorporates target fragments from Bcerg1, Bcerg2, and Bcerg27. Nevertheless, the Bcerg1 dsRNA alone achieved greater disease suppression than the chimeric Bcergi dsRNA. Conclusions Here, we developed a highly efficient and scalable method for producing chimeric dsRNAs in E. coli HT115 (DE3) in research laboratories using our homemade pSIG plasmid vectors. This approach addresses key challenges in SIGS research, including the need to produce large quantities of dsRNA and identify effective dsRNAs, thus enhancing the feasibility of SIGS as a sustainable strategy for controlling plant diseases and pests in crops.